Biopower, Biopolitics, Biosemiotics: Entangling Mortalities and Moralities - Anderson, Myrdene; Bisanz, Elize (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2019)
While biosemiotics moves in the direction of liberating both biology and semiotics from strict observance of the paradigms of the 19th and 20th centuries – via evo-devo-eco models and the ontological turn – we propose a glance backwards as well as a sharper focus on the social and sexual conditions of the present and foreseeable future. We bring together contemporary discourses on feminism, biophilia, biophobia, essentialisms, and denial, with the prescient ideas of biopower developed by Michel Foucault with respect to the nation-state. He addressed a bevy of pathologies endemic in the societies he witnessed at that time; these conditions persist and indeed have flourished, ranging from sexism, to racism, to classism, to technologism, to the outsourcing of work and the exporting of refuse, to the addictive mantra of “sustainability”, all culminating in society’s exercising of power over both life and death, both living and dying, both near and far. We also find biopower a suitable critical lens for pursuing the pathologies surrounding population – population as generated, as regulated, as ignored, as denied, whether or not acknowledged as being the work of wombs.